Tunneling-tip-induced collapse of the charge gap in the excitonic insulator Ta_{2}NiSe_{5} - Qingyu He; Xinglu Que; Lihui Zhou; Masahiko Isobe; Dennis Huang; Hidenori Takagi (Physical Review Research, 2021)
Tuning many-body electronic phases by an external handle is of both fundamental and practical importance in condensed matter science. The tunability mirrors the underlying interactions, and gigantic electric, optical and magnetic responses to minute external stimuli can be anticipated in the critical region of phase change. The excitonic insulator is one of the more exotic phases of interacting electrons, produced by the Coulomb attraction between a small and equal number of electrons and holes, leading to the spontaneous formation of exciton pairs in narrow-gap semiconductors/semimetals. The layered chalcogenide Ta_{2}NiSe_{5} has been recently discussed as a candidate for the excitonic insulator, though the nature of the excitation gap that opens below T_{c}=328K remains hotly debated. Here, we demonstrate a drastic collapse of the excitation gap in Ta_{2}NiSe_{5} and the realization of a zero-gap state by moving the tip of a cryogenic scanning tunneling microscope towards the sample surface by a few angstroms. We argue that the collapse of the gap is driven predominantly by the electrostatic charge accumulation at the surface induced by the proximity of the tip and the resultant carrier doping. The fragility of the gap in the insulating state of Ta_{2}NiSe_{5} strongly suggests the gap possesses many-body character. Our results establish a reversible phase-change function based on Ta_{2}NiSe_{5}.